2019
DOI: 10.1071/sh18150
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis B prevalence in Australian Aboriginal and Torres Strait Islander people before and after implementing a universal vaccination program: a systematic review and meta-analysis

Abstract: Background: A higher prevalence of chronic hepatitis B (CHB) has been reported in Aboriginal and Torres Strait Islander (Aboriginal) compared with non-Aboriginal Australians. An Australian infant and adolescent hepatitis B virus (HBV) vaccination program was implemented in 2000. Meta-analysis methods will be used to examine if the pooled prevalence of CHB decreased after 2000 among Aboriginal Australians. Methods: Embase, Medline and Web of Science were searched from 1 January 1981 to 29 March 2018 and all iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 51 publications
(240 reference statements)
2
13
1
1
Order By: Relevance
“…Limitations to the model arise where there is unavailability of, or uncertainty in, source data. This particularly applied to prevalence estimates by age for priority populations, including Aboriginal and Torres Strait Islander peoples . Work to establish more rigorous estimates, and to apply these together with specific natural history and treatment coverage data to a dedicated model simulating CHB in Aboriginal and Torres Strait Islander Australians, is ongoing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations to the model arise where there is unavailability of, or uncertainty in, source data. This particularly applied to prevalence estimates by age for priority populations, including Aboriginal and Torres Strait Islander peoples . Work to establish more rigorous estimates, and to apply these together with specific natural history and treatment coverage data to a dedicated model simulating CHB in Aboriginal and Torres Strait Islander Australians, is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline prevalence in the model incorporates the population of Australia in 1951, preceding the onset of substantial migration from intermediate and high CHB populations. Whereas baseline prevalence includes both Aboriginal and Torres Strait Islander Australians (who have a significantly higher prevalence of CHB) and non‐Indigenous Australians, specific modeling of CHB in Indigenous Australians was not included. The number of people living with CHB migrating to Australia each year was derived using the estimated prevalence of CHB according to COB.…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol misuse and smoking are common among Australians, including Aboriginal peoples, and contribute to liver fibrosis progression and carcinogenesis 13 . Prevalence rates of viral hepatitis are higher among Aboriginal peoples than the rest of the Australian population 14,15 . Hepatitis B virus (HBV) infection is reported at four times the rate among Aboriginal peoples (4%) compared with the rest of the Australian population (1%) and is the primary aetiology in 40.5% of HCC patients 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence rates of viral hepatitis are higher among Aboriginal peoples than the rest of the Australian population 14,15 . Hepatitis B virus (HBV) infection is reported at four times the rate among Aboriginal peoples (4%) compared with the rest of the Australian population (1%) and is the primary aetiology in 40.5% of HCC patients 14 . Moreover, Aboriginal peoples have a more aggressive HBV genotype (C4) associated with rapid progression of liver disease and HCC risk 16 .…”
Section: Introductionmentioning
confidence: 99%
“…CHB disproportionately affects Indigenous populations globally [2] and this is similar in Australia. A recent systematic review and meta-analysis showed an overall prevalence of 10.8% in pre and 3.5% in post-universal vaccination populations in Aboriginal and Torres Strait Islander people (hereafter respectfully referred to as Aboriginal) in Australia [3]. CHB is endemic in Aboriginal people of the Northern Territory (NT) of Australia, with a contemporary estimated prevalence of 6.1% [4].…”
Section: Introductionmentioning
confidence: 99%